ETNOMATEMATIKA JEMBATAN EFEKTIFITAS IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS KONSTRUKTIVISME PADA KURIKULUM 2013 - Nandang Arif Saefuloh; Lilim Halimah (UJMES (Uninus Journal of Mathematics Education and Science), 2021)
The implementation of constructivism learning goes wrong when an important part of it is forgotten, namely Scaffolding which should be integrated in every constructivism-based learning, and one form of Scaffolding is to apply ethnomathematics in its implementation, so ethnomathematics can be a bridge to achieve constructivism-based learning effectiveness.